2002
DOI: 10.1007/s00330-002-1396-0
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injuries: imaging and intervention in post-traumatic complications (delayed intervention)

Abstract: The nonoperative management (NOM) of abdominal trauma has gained increasing acceptance over the past decade. This approach has been extended to severe trauma patients previously considered as candidates for surgery. Consequently, the incidence of delayed and uncommonly encountered complications has increased. Causes of delayed complications are multiple and include: (a) abnormal or insufficient injury healing process; (b) retention of necrotic tissue; (c) secondary infection of initially sterile collections; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 159 publications
0
45
0
5
Order By: Relevance
“…Nonsurgical management of abdominal trauma has gained increasing acceptance in mild trauma patients, and this approach has been expanded for use in severe patients previously considered as candidates for surgery (15). Angiography and TAE may have an important role in the diagnosis and treatment of mesenteric bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonsurgical management of abdominal trauma has gained increasing acceptance in mild trauma patients, and this approach has been expanded for use in severe patients previously considered as candidates for surgery (15). Angiography and TAE may have an important role in the diagnosis and treatment of mesenteric bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, renal artery embolization was performed to control renal bleeding in one patient (Patient 6). TAE for traumatic hepatic, splenic, and renal injury and pelvic fracture was reported to be a safe and effective treatment (15,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that pseudoaneurysm is even bigger than the aorta. only 13 well reported cases [2][3][4][5][6][7][8][9][10][11][12][13] of this complication in the recent English literature searching in Medline (http://www.ncbi.nlm.nih.gov/entrez/query.fcgi) (Table 1 shows 12 cases; Owens [13] reported the last case, not included because the pseudoaneurysm has already ruptured).…”
Section: Discussionmentioning
confidence: 99%
“…Biliäre Komplikationen können unterteilt werden in Bilhämie, Galleleckagen, Biliome, biliäre Sepsis und Gallengangsstrikturen [30].…”
Section: Biliäre Komplikationenunclassified